Hydro-mechanical behavior of a lateritic fiber-soil composite as a waste containment liner. Issue 1 (February 2019) - Ehrlich, M.; Almeida, M.S.S.; Curcio, D.
Abstract: In waste disposal landfill projects, the hydraulic conductivity of the barriers is a major consideration. The use of fibers mixed with backfill may improve the overall performance of the barriers. Fiber-soil composites show a more resistant and ductile behavior than the soil alone. The presence of fibers may reduce cracking problems related to shrinkage or traction in liners or covers. In this study, laboratory tests were performed to evaluate the use of fiber-soil composites as a containing barrier. Hydraulic conductivity and diametral-compression tests were carried out on PET fiber reinforced and unreinforced compacted soil specimens. The tests were conducted under confinement conditions similar to those found in the field. Diametral-compression tests were used to induce cracks in the specimens. Hydraulic conductivity was measured at different stages during the diametral loading. In the tests performed under low confinement pressure (10 kPa), the crack openings led to a significant increase in hydraulic conductivity. The results showed that the addition of fibers increases the tensile strength of the soil-fiber mass and delays the opening of cracks. Moreover, in the tests under high confinement pressure (100 kPa), a decrease in hydraulic conductivity occurred at all stages of the diametral load application.